PENINGKATAN PENGETAHUAN PEMELIHARAAN KESEHATAN GIGI DAN MULUT PADA SISWA DAN ORANG TUA DI SLB-B NEGERI GARUT MENGGUNAKAN MEDIA VIDEO INTERAKTIF - Chaerudin, Denden Ridwan; Fatimah, Siti; Praptiwi, Yenni Hendriani (Poltekkes Kemenkes Bandung, 2024)
Oral diseases, including dental caries and diseases of the tooth-supporting tissues, often stem from neglect of oral hygiene. A primary contributing factor is the lack of knowledge about proper tooth-brushing techniques. To address this issue, interactive video media was utilized to make the delivery of tooth-brushing knowledge more engaging. School-age children were the most affected group by oral and dental diseases. This community service initiative aimed to enhance the understanding of oral health among students and their parents through a partnership program. A total of 26 students and 19 parents participated in the program. Pre-counseling evaluations revealed that students had an average knowledge score of 25%, while parents scored 37%. Post-counseling, the average knowledge scores increased to 57% for students and 61% for parents. The assessment of tooth-brushing skills showed an average score of 57.7%, categorized as moderate. These findings demonstrate that both students and parents significantly improved their knowledge of oral health maintenance, with students achieving moderate proficiency in tooth-brushing techniques.